RESISTANCE OF FOUR DIFFERENT LOCAL HYBRID CHICKENS TO INFECTIOUS BURSAL DISEASE INFECTION - Al-Zuhairy, M. A. (The Iraqi Journal of Veterinary Medicine, 2021)
Four hundred, one day old chicks, of four hybrids, were divided into four groups, reared on the floor for ten weeks. The hybrids were vaccinated with live IBD vaccine at 14, 35, 56 days. Maternal antibody titers, antibody titer after each vaccination and bursa index were measured. Results revealed that the Barred local hybrid showed a highest maternal antibody titer and antibody titer after each vaccination, more bursa index lowest mortality. Highly significant correlation (P<0.01) & more linear regression between antibody titer & maternal antibody titers were observed in the barred hybrids.